Fungal community assembly in soils and roots under plant invasion and nitrogen deposition. (August 2019) - Phillips, Michala L.; Weber, Sӧren E.; Andrews, Lela V.; Aronson, Emma L.; Allen, Michael F.; Allen, Edith B.
Abstract: Fungal community composition in the Anthropocene is driven by rapid changes in environmental conditions caused by human activities. This study examines the relative importance of two global change drivers – atmospheric nitrogen (N) deposition and annual grass invasion – on structuring fungal communities in a California chaparral ecosystem, with emphasis on arbuscular mycorrhizal fungi. We used molecular markers, functional groupings, generalized linear statistics and joint distribution modeling, to examine how environmental variables structure taxonomic and functional composition of fungal communities. Invasive grasses had a lower richness and relative abundance of symbiotic fungi (both AMF and other fungi) compared to native shrubs. We found a higher richness and abundance of rhizophilic (e.g. Glomeraceae) and edaphophilic (e.g. Gigasporaceae) AMF with increasing soil NO3 . Our findings suggest that invasive persistence may decrease the presence of multiple soil symbionts that native species depend on for pathogen protection and increased access to soil resources.